156k views
1 vote
If l = 2(w + 1), which of the following correctly gives w in terms of l?

Answer?

User Rainbacon
by
4.8k points

2 Answers

4 votes

Solution:

Simplify the equation and solve for w.

  • l = 2(w + 1)
  • => l = 2w + 2
  • => l - 2 = 2w
  • => l/2 - 2/2 = 2w/2
  • => l/2 - 1 = w

The value of w is l/2 - 1 .

User Janis
by
4.6k points
5 votes

Answer:


w=\frac12I-1

Or
w=\frac12(I-2)

(both are correct - just different ways of writing the equation)

Explanation:


I = 2(w + 1)

Expand the bracket:


\implies I = 2w + 2

Subtract 2 from both sides:


\implies I - 2 = 2w + 2 - 2\\\\\implies I - 2 = 2w

Divide both sides by 2:


\implies (I-2)/(2)=(2w)/(2)


\implies w=\frac12I-1

User Edisonthk
by
5.1k points